(untitled) (Papeles, 2023)
In the article, reflections on the social service to minors by agents who have overturned, in the publications of the School of Social Service of Santa Fe and in the first provincial days of Social Service (1947), different meanings about the child social issue and suggestions for its approach. Publications from the years 1946-1948 and documents on government institutions in the mid-twentieth century at the national and provincial level are addressed. Between the decades of the ’30s and ’40s, the emergence of the Juvenile Courts, the Secretary of Welfare and Social Security and the opening of the Schools of Social Service in the province coincide. The theoretical-practical arguments that are reflected in the publications are analyzed to glimpse the complexity and tensions of approaching the problems and their implications in the configuration of social-assistance bureaucracies oriented to child protection. What is interesting to replace here is a possible analytical path on the professionalization of Social Work through reviewing the technical-scientific knowledge put into play, the particular demands and the vocational and moral meanings that the agents attributed to their practices and to the recipients of them.